Assessment of risk of intussusception after pilot rollout of rotavirus vaccine in the Indian public health system. Issue 33 (14th July 2020) - ,; Bhandari, Nita; Antony, Kalpana; Balraj, Vinohar; Rongsen-Chandola, Temsunaro; Kumar, Tivendra; Sinha, Bireshwar; Goyal, Nidhi; Guleri, Rajesh; Bavdekar, Ashish; Juvekar, Sanjay; Dayma, Girish; et al.
Highlights: Prelicensure trials of ROTAVAC® not powered to assess risk of intussusception. During ROTAVAC® rollout we assessed risk of intussusception in infants in 3 states. No increased risk of intussusception within 21 days of 1st and 2nd dose. No increased risk of intussusception within 21 days of any single dose or all 3 doses. Abstract: Background: Pre-licensure trials of ROTAVAC® were not adequately powered to assess risk of intussusception, a rare adverse event associated with other rotavirus vaccines in some settings. We examined the risk of intussusception after ROTAVAC® vaccination among Indian infants during pilot rollout of the vaccine in the public health system in three states - Himachal Pradesh, Maharashtra and Tamil Nadu. Methods: Passive surveillance for intussusception was set up in 35 sentinel health facilities covering 26.3 million population in the three states under monitoring of an Interministerial-Interagency Steering Committee. Clinical and immunization data were collected by independent teams. An expert committee blinded to vaccination status, classified intussusception cases using Brighton criteria. The self-controlled case-series method was used to estimate risk of intussusception (Brighton Level 1) after ROTAVAC® vaccination. Results: 151 intussusception cases were included in the analysis. The relative incidence (incidence during the risk period compared to the control period) 1–21 days after doses 1 and 2 combined was 1.56 (95% CI, 0.0–5.28) and that for three doses combined was 1.88 (95% CI, 0.76–4.30). Attributable risk 1–21 days after doses 1 and 2 combined was 0.11 (95% CI, 0.0–0.25) and that for 3 doses combined was 0.42 (95% CI, 0.0–0.70) per 100, 000 doses. Conclusions: No increased risk of intussusception within 21 days of receipt of the first two doses combined or all 3 doses combined of ROTAVAC® was detected.